Reliability of the measures inter and intra-evaluators with universal goniometer and fleximeter - Victor Hugo de Oliveira Gouveia; Ana Gabriela de Figueiredo Araújo; Simone dos Santos Maciel; José Jamacy de Almeida Ferreira; Heleodório Honorato dos Santos (Universidade de São Paulo, 2014)
The objective of this study was to analyze the reliability of the intra and inter-evaluators measures, with universal goniometer and fleximeter. Eighty university students (45 women and 35 men [average±SD]; age: 20.81±2.63 years, body mass: 68.36±16.31 kg, height: 1.69±0.09 m, BMI: 23.88±4.15 kg/m2) were submitted to goniometry and fleximetry of elbow and knee flexion, ankle dorsiflexion and wrist extension. It was calculated the intraclass correlation coefficient (ICC), considering a significance level of 5%. Overall, the results showed very strong (ICC: 0.91≤0.99; P<0.001) and strong (0.75≤0.90; P<0.001) correlations in all movements, intra and inter-evaluators. On inter-correlation instruments, there are strong coefficients on all measures (0.75≤0.90; P<0.001) for the two instruments. In the studied movements, the evaluator experience did not influence the measurements and both the universal goniometer and the fleximeter showed high reliability.